The future of oral hormonal contraception - Rabe, Thomas; Runnebaum, Benno (Fertility control, 1999)
Each second, the world population increases by three newborn babies (98 million per year); nine out of ten are born in developing countries. In 2050, the total population will be 12.5 billion instead of the 6 billion of today. No war, no disease, but only access to and the acceptance of effective methods of fertility control can stop the growth of the world population. Additionally, religious aspects, the realisation of female rights, equal access to education and jobs for women and men, availability of pensions (no further need for support by a big family) will be the pillars of a successful family policy. Furthermore, a better health care system for women (500,000 deaths annually during pregnancy and childbirth) and safe techniques of pregnancy termination (200,000 deaths annually per 50 million abortions) are necessary. Oral hormonal contraceptives (OCs) are one of the methods of fertility control which is highly effective, safe, well accepted and available in most countries worldwide.